Fulfillment of Buyer's Liability Compensation Claim That is Not Granted for The Seller's Default in The Land Sale and Purchase Agreement - Eko Rial Nugroho; Rohidin Rohidin (Faculty of Law, Universitas Pekalongan, 2025)
The focus of this research study is to discuss the fulfillment of the buyer's claim for compensation for the seller's default in the land sale and purchase agreement. The purpose of the research was to analyze the fulfillment of the buyer's liability compensation claim that was not granted for the seller's default in the land sale and purchase agreement. This type of research is normative juridical research, with a statutory approach and a case approach. The research data source uses secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. Research data collection by literature studies and document studies as well as qualitative analysis. This study concludes that the seller's liability for default against the buyer in the land sale and purchase agreement is the fulfillment of the buyer's liability for the seller's default in the land sale and purchase agreement cannot be granted because the claim for the right to compensation is not requested or not included in the lawsuit. The examining judge cannot consider granting the claim for the right to compensation applied for. If the claim for damages is included or requested in the lawsuit, at least the examining judge can consider the claim for the right to compensation, especially by detailing the list of losses that have occurred, both concerning losses suffered as a result of default and lost profits.